2022
DOI: 10.1155/2022/6098191
|View full text |Cite
|
Sign up to set email alerts
|

ProNGF/NGF Modulates Autophagy and Apoptosis through PI3K/Akt/mTOR and ERK Signaling Pathways following Cerebral Ischemia-Reperfusion in Rats

Abstract: NGF is involved in the process of autophagy; however, the underlying mechanisms of proNGF/NGF on autophagy in cerebral ischemia-reperfusion (CIR) remain unclear. This study explored the potential pathway of proNGF/NGF in mediating autophagy and apoptosis and thereby contributed to poststroke neurological rehabilitation. In this study, PC12 cell lines and male SD rats were used to simulate CIR; it was found that within 24 h reperfusion, proNGF was the predominant form of Ngf while after 24 h NGF was produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Notably, we observed that the ERK signaling inhibitor PD98059 blocked the conversion of LC3 induced by CCN1, suggesting that CCN1 activates autophagic flux by inducing the MAPK/ERK pathway. In recent literatures, the positive regulation of autophagy by the ERK pathway has been reported, but the underlying mechanism remains unclear and may be listed as followings 28,41 . On one hand, phosphorylation of ERK can inhibit mTOR, thereby promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we observed that the ERK signaling inhibitor PD98059 blocked the conversion of LC3 induced by CCN1, suggesting that CCN1 activates autophagic flux by inducing the MAPK/ERK pathway. In recent literatures, the positive regulation of autophagy by the ERK pathway has been reported, but the underlying mechanism remains unclear and may be listed as followings 28,41 . On one hand, phosphorylation of ERK can inhibit mTOR, thereby promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent literatures, the positive regulation of autophagy by the ERK pathway has been reported, but the underlying mechanism remains unclear and may be listed as followings. 28,41 On one hand, phosphorylation of ERK can inhibit mTOR, thereby promoting autophagy. Increased pERK1/2 downregulates the phosphorylation level of p70S6K, one of the mTORC1 substrates, thereby inhibiting mTORC1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that action balance of proNGF/NGF is critical for poststroke neurological rehabilitation. Using cerebral ischemia-reperfusion (CIR) models with PC12 cell lines or rats, Li et al found that proNGF was predominant within 24 h reperfusion, followed by mature NGF production from the proNGF [ 54 ]. As expected, the mature NGF had a neuroprotective effect against autophagic and apoptotic damage after the CIR; however, proNGF contributed to both autophagic and apoptotic processes.…”
Section: Neurotrophin Synaptic Function and Neurogenesismentioning
confidence: 99%
“…As expected, the mature NGF had a neuroprotective effect against autophagic and apoptotic damage after the CIR; however, proNGF contributed to both autophagic and apoptotic processes. In their system, the PI3K/Akt/mTOR and ERK pathway contributed to the neuroprotection through a mature form of NGF, while the proNGF stimulated the ERK pathway, resulting in increasing autophagy and apoptosis [ 54 ]. Thus, a TrkA-specific agonist (for example, ENT-A013) may be beneficial for neuroprotection against proNGF/p75NTR-dependent cell damage after CIR.…”
Section: Neurotrophin Synaptic Function and Neurogenesismentioning
confidence: 99%
“…The PI3K-Akt signalling pathway plays a crucial role in regulating various cellular functions, including neuronal survival and morphology, and can be modulated by growth factors and neurotrophic factors. [16][17][18][19] Activation of the Akt/GSK3β pathway has been associated with the development and treatment of several diseases. [20][21][22] In developing neurons Akt regulates downstream GSK3β phosphorylation, which drives axon speci city by inhibiting GSK3β via the PI3K-Akt pathway.…”
Section: Introductionmentioning
confidence: 99%